Risk Factors for Cerebral Plasy - Demeši Drljan, Čila; Mikov, Aleksandra; Krasnik, Rastislava; Knežević, Aleksandar; Zvekić-Svorcan, Jelena; Mikov, Igor (Vojnosanitetski pregled, 2023)
Background/Aim. Cerebral palsy (CP) etiology is multifactorial and heterogeneous, manifesting as damage to the developing brain. The associated risk factors can arise in the prenatal, perinatal, or postnatal period. The aim of this study was to determine the risk factors for CP and examine the associations between CP type, gestational age, and perinatal risk factors. Methods. The study sample comprised 206 children with CP. Pertinent data were collected from medical records and included participants’ gestational age at birth, medical history, and CP clinical characteristics. Risk factors were divided according to the timing of brain injury into prenatal, perinatal, and neonatal. Results. Hormonally maintained pregnancy (55.3%), twin pregnancy (28.9%), vaginal bleeding after the 20th week of gestation (21.1%), threatened abortion in the first half of pregnancy (13.2%), and maternal infection (10.5%) were identified as the main prenatal risk factors for CP. Prematurity (54.5%) was the leading perinatal risk factor, followed by low birthweight (50.8%), Apgar score < 7 (41.7%), assisted delivery (41.4%), and breech presentation (13.5%). Respiratory distress syndrome (16%), need for treatment in the Neonatal Intensive Care Unit (22.3%), assisted ventilation (18.4%), hypoxic-ischemic encephalopathy (11.2%), and neonatal convulsions (5.8%) were identified as the leading neonatal risk factors for CP. A statistically significant difference was found in the total number of perinatal risk factors in relation to gestational age (p < 0.001) and CP type (p = 0.006). Perinatal risk factors were most prevalent in preterm infants and children affected by the CP of spastic bilateral type. A statistically significant difference was noted in the distribution of CP types depending on the gestational age (p < 0.001). In particular, spastic bilateral CP type was most prevalent in the group of preterm-born children. Conclusion. CP is characterized by heterogeneous risk factors and is a result of interaction among multiple risk factors.